Isolation of poliovirus shedding following vaccination in children with antibody deficiency disorders - Galal, Nermeen M; Bassiouny, Laila; Nasr, Eman; Abdelmeguid, Naglaa (The Journal of Infection in Developing Countries, 2012)
Introduction: Prolonged excretion of oral poliovirus may occur in primary antibody deficiency states. Those patients who persistently excrete the virus may pose the risk of aiding viral propagation in the environment. This study therefore aimed to identify the potential for prolonged poliovirus shedding by patients diagnosed with congenital antibody deficiency disorders. Methodology: A cohort of children later diagnosed with antibody deficiency disorders was included in the study. Patient history was taken for each participant, with emphasis on vaccination data. Laboratory investigations included immunoglobulin profiles and stool sample collection at one month intervals from each patient, with follow-up for six months. The virus isolates were detected using enzyme-linked immunosorbent assay (ELISA) and molecular reverse transcription polymerase chain reaction (RT-PCR) techniques. Results: On the initial sample screens, one patient revealed excretion one for Sabin-like strain 1 (SL1) and one patient revealed excretion for Sabin like strain 2 (SL2). Only one patient continued to shed the virus (SL1) on three successive samples and on follow-up. There was no correlation between the level of immunoglobulins and duration of virus shedding. Conclusion: The study demonstrates the low occurrence of prolonged vaccine polioviruses shedding in a group of children exposed to a live vaccine.